EXISTENCE OF THE VIDARBHI FILM INDUSTRY: AN ANALYTICAL STUDY - Khule, Abhishek (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Nagpur - Recently, the announcement of the establishment of a film city in Vidarbha has been made. Naturally, it is a welcome development for the region and its cultural field. However, whether it will materialize or not, and what the challenges and obstacles ahead are, this research paper attempts to explore. Vidarbhi artists should not limit themselves by drawing boundaries around themselves. Following the saying "This world is my home," one should think broadly about how their artwork can reach the entire world without placing any specific "tag" on it. However, it is evident from this research that this is not happening effectively. In this study, I have referred to interviews with experts in the field and some published literature.